2022
DOI: 10.1002/ccr3.5309
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of creatine kinase in acute pancreatitis: A case report

Abstract: Creatine kinase (CK/CK‐MB) testing is an essential laboratory test approaching a patient with chest or epigastric pain. We report a 38‐year‐old man with acute pancreatitis and elevated CK/CK‐MB level without myocardial involvement. Acute pancreatitis may be considered as a false‐positive cause of CK/CK‐MB test in patients presenting with chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An increase in CK can be seen in SAP, which may be a predictive factor for SAP. 42 In our research, several scores including Ranson, BISAP and SOFA were compared with our nomogram, which showed that the predictive performance of the nomogram model in our study was the best. Previous research showed that Ranson, BISAP and SOFA scores have been applied widely for evaluating the disease severity in AP.…”
mentioning
confidence: 67%
“…An increase in CK can be seen in SAP, which may be a predictive factor for SAP. 42 In our research, several scores including Ranson, BISAP and SOFA were compared with our nomogram, which showed that the predictive performance of the nomogram model in our study was the best. Previous research showed that Ranson, BISAP and SOFA scores have been applied widely for evaluating the disease severity in AP.…”
mentioning
confidence: 67%
“…Previously only several case reports considered the potential role of CK in AP development. In 2022, Sheibani et al described a case of a 39-year-old man with AP where the CK activity peaked the day after admission but returned to normal 5 days after the admission ( 22 ). Karachaliou et al described a case report of a 64-year-old woman whose increased CK levels normalized throughout hospitalization in total of 12 days ( 23 ).…”
Section: Discussionmentioning
confidence: 99%